2014
DOI: 10.1039/c4sm01038h
|View full text |Cite
|
Sign up to set email alerts
|

The role of substrate pre-stretch in post-wrinkling bifurcations

Abstract: When a stiff film on a soft substrate is compressed, the surface of the film forms wrinkles, with tunable wavelengths and amplitudes that enable a variety of applications. As the compressive strain increases, the film undergoes post-wrinkling bifurcations, leading to period doubling and eventually to formation of localized folds or ridges. Here we study the post-wrinkling bifurcations in films on pre-stretched substrates. Through a combination of experiments and simulations, we demonstrate that pre-stretched s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 53 publications
12
51
0
Order By: Relevance
“…(16) indicates that ε PD is a linear function of the pre-stretch; moreover, the variation of the modulus ratio makes no difference to the proportion, which further corroborates that the effect of the modulus ratio can be neglected. These trends are in accordance with the experiment and simulation carried by Auguste et al [36]. If the substrate is not pre-stretched (λ 0 1 ¼ 1), it can be seen from Eq.…”
Section: The Onset Of Period-doubling Instabilitysupporting
confidence: 78%
See 1 more Smart Citation
“…(16) indicates that ε PD is a linear function of the pre-stretch; moreover, the variation of the modulus ratio makes no difference to the proportion, which further corroborates that the effect of the modulus ratio can be neglected. These trends are in accordance with the experiment and simulation carried by Auguste et al [36]. If the substrate is not pre-stretched (λ 0 1 ¼ 1), it can be seen from Eq.…”
Section: The Onset Of Period-doubling Instabilitysupporting
confidence: 78%
“…Given that the maximum strain in this study is as large as $ 0.3, both the film and the substrate are modeled as a hyperelastic solid. The incompressible neo-Hookean constitutive model provides a good description of the hyperelastic materials within the range of strain considered here [25,36]. The hybrid plane strain quadrilateral element (CPE8RH) is adopted and the meshes near the film/substrate interface are refined.…”
Section: Numerical Simulations Of the Post-buckling Modesmentioning
confidence: 99%
“…Such elastomeric materials with strains under 0.5 are commonly described by the neo-Hookean model, which has led to good agreement with experiments in previous work [37,39,41,46], thus we model both the film and substrate as incompressible neo-Hookean materials, with perfect bonding between the layers. We set the total thickness of the bilayer to be 50 times the film thickness so that the substrate is effectively infinite.…”
Section: Finite Element Simulationssupporting
confidence: 50%
“…However, their simulations could not continue past the onset of creases. In addition, both studies reported by Wang, et al [28,41], and Tallinen, et al [42], involve differential pre-stretch of the substrate compared to the film, which is known to have important effects on post-wrinkling behavior [37,44,45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation